Building resistance to the ‘GERM’: Discourse Theory, Discursive Struggle and the ‘teacher’ subject position - Salter, Leon (Massey University, 2014)
In April 2013 the NZEI (New Zealand Educational Institute), the trade union which provides representation and advocacy to around 50,000 primary and ECE teachers and support staff, mobilized around 8,000 of its members and sympathizers in coordinated protest marches across the country. Promotion posters for the rally emphasized not the stalled collective agreement negotiations, but concern “about the impact the Government’s education policies are having on children and their learning” (NZEI, 2013). The NZEI’s ‘Stand Up For Kids: Protect Our Schools’ campaign site (http://www.standupforkids.org.nz/g-e-r-m/) characterizes the government’s reform programme as part of the GERM; the Global Education Reform Movement, a term coined by the Finnish education expert Pasi Sahlberg (Sahlberg, 2013). The NZEI’s web-page contains an illustration image of the ‘GERM’ as an actual germ, a ghoulish monster dripping with slime and significantly carrying a briefcase, together with a dichotomized outline of the two sides of the debate from Sahlberg’s blog; ‘Standardization’ versus ‘Personalized Learning’, ‘Competition’ versus ‘Collaboration’ etc. Utilizing concepts from Ernesto Laclau and Chantal Mouffe’s Discourse Theory (Laclau & Mouffe 1985; Laclau 1990, 2005), this PhD study, as yet in its early stages, will aim to theorize the ‘Stand Up For Kids: Protect Our Schools’ campaign as a hegemonic, or discursive struggle, which discursively constructs an ‘antagonistic frontier’ with a ‘constitutive outside’ in the GERM. ‘Empty signifiers’ such as ‘Teacher’, ‘School’ and ‘Kids’ become the discursive space where the two articulations compete to attain objectivity; relatively stable ‘common-sense’ understandings, while at the same time constituting antagonistic identities on both sides of the argument. [From the Introduction]
Keywords: Education; Primary sector; Educational reform; New Zealand; Discourse theory